Tackling Inequalities in Access to Medicines for People Experiencing Homelessness: A Meta‐Ethnography and Qualitative Systematic Review - Tasnim Begum; Kylie Murrell; Anna Robinson‐Barella (Wiley, 2024)
ABSTRACT Introduction Despite increased awareness of the detrimental relationship between homelessness and health, people experiencing homelessness remain an underserved population in health and social care research. Due to barriers affecting the accessibility of medicine and healthcare services, as well as reported competing priorities such as food and shelter, evidence has demonstrated that people experiencing homelessness are less likely to undergo routine examinations, receive diagnoses and adhere to prescribed medical treatments. To enhance service design and access for those experiencing homelessness, it is critical to better recognise, understand and address the barriers these individuals face. This meta‐ethnography aims to identify barriers, enablers and interventions to begin addressing this inequality gap. Methods A systematic literature search was undertaken in October and re‐ran in December 2023 across four databases: MEDLINE, Embase, CINAHL and Scopus. Qualitative studies were included if they addressed barriers, enablers and interventions aimed at tackling medicines and health service inequalities among populations experiencing homelessness. Study quality was assessed using the Joanna Briggs Institute critical appraisal checklist. Data were synthesised using a meta‐ethnographic approach, as outlined by Noblit and Hare. The review was registered on PROSPERO (CRD42024511502) and performed according to PRISMA guidelines. Results This meta‐ethnographic systematic review synthesised data from eight studies across multiple countries. Three overarching third‐order constructs (termed 'themes') were developed through reciprocal translation and centred around: recognising and acknowledging the discrimination, stigma and barriers experienced when using current services; exploring safe and practical use of medicines and the promotion of general health education and appreciating strategies to tackle inequalities, namely community outreach programmes designed for homeless communities. Conclusion This work highlighted the barriers, enablers and interventions that sought to address the inequalities affecting people experiencing homelessness in accessing medication and healthcare services. Future research should utilise lived‐experience narratives and co‐design to further explore ways to tackle wider healthcare accessibility inequalities for this minoritised population. Trial Registration Not applicable, as this is a systematic review. Patient or Public Contribution Public contributors (minority research champions and one public health research champion, H.K.G. and T.G.) informed and shaped this project during study design and conceptualisation. They helped to ensure that the study was conducted, and the findings were reported with sensitivity.